(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This study examined the relationship between of time management and service delivery of health centres in Bonny Island, Rivers State. The study adopts a survey research design. The study is limited to sixty-three (63) staffs of selected healthcare centres in bonny island. The data generated were analyzed using descriptive statistics and Pearson correlation analysis. The hypotheses formulated were tested using multiple regression analysis. The result of regression analysis shows that found a significant relationship between queuing setting and priority setting on prompt service delivery in health care centres in Bonny Local Government Area, while an insignificant effect on goal setting, work schedule and multitasking on prompt service delivery in health care centres in Bonny local government area. The study concludes that effective time management does play a critical role in enhancing service delivery in public health centres, but its impact is largely dependent on the specific strategies applied and the context within which they operate. Particularly, priority setting and improved queuing systems should be considered strategic focal points for improving healthcare outcomes in Bonny Local Government Area. The study therefore recommends that proper task prioritization ensures that the most critical needs are addressed promptly, leading to improved patient satisfaction and outcomes and healthcare centres introduce structured or electronic queuing systems, especially in high-traffic clinics.